Behavioral Mechanisms, Elevated Depressive Symptoms, and the Risk for Myocardial Infarction or Death in Individuals with Coronary Heart Disease (A Reason for Geographic and Racial Differences in Stroke [REGARDS] Study) - Ye, Siqin (2013)
OBJECTIVE: To determine whether behavioral mechanisms explain the association between depressive symptoms and myocardial infarction (MI) or death in individuals with coronary heart disease (CHD). BACKGROUND: Depressive symptoms are associated with increased morbidity and mortality in individuals with CHD, but it is unclear how much behavioral mechanisms contribute to this association. METHODS: The study included 4,676 participants with a history of CHD. Elevated depressive symptoms were defined as scores ≥4 on the Center for Epidemiologic Studies Depression 4-item Scale. The primary outcome was definite/probable MI or death from any cause. Incremental proportional hazards models were constructed by adding demographics, comorbidities and medications, then four behavioral mechanisms (alcohol use, smoking, physical inactivity, and medication non-adherence). RESULTS: At baseline, 638 (13.6%) participants had elevated depressive symptoms. Over a median 3.8 years of follow up, 125 of 638 (19.6%) participants with and 657 of 4038 (16.3%) without elevated depressive symptoms had events. Higher risk of MI or death was observed for elevated depressive symptoms after adjusting for demographics (hazard ratio [HR] 1.41, 95% CI 1.15–1.72), but was no longer significant after adjusting for behavioral mechanisms (HR 1.14, 95% CI 0.93–1.40). The four behavioral mechanisms together significantly attenuated the risk for MI or death conveyed by elevated depressive symptoms (−36.9%, 95% CI −18.9 to −119.1%), with smoking (−17.6%, 95% CI −6.5% to −56.0%) and physical inactivity (−21.0%, 95% CI −9.7% to −61.1%) having the biggest explanatory roles. CONCLUSION: Our findings suggest potential roles for behavioral interventions targeting smoking and physical inactivity in patients with CHD and comorbid depression.